2008
DOI: 10.1007/s11695-008-9597-5
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Force and Force Control After Weight Loss in Obese and Morbidly Obese Men

Abstract: Despite a large force loss, particularly for the lower limbs in morbidly obese individuals after surgery, this loss is relatively well tolerated because the relation between force and body weight is even improved and the ability to maintain that force is preserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 36 publications
4
51
0
3
Order By: Relevance
“…All trials within each condition lasted 30 s and the averages of the four trials were used for data analysis. Postural data for some subjects from both the control and the obese group have been published elsewhere [1,6].…”
Section: Postural Sway Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…All trials within each condition lasted 30 s and the averages of the four trials were used for data analysis. Postural data for some subjects from both the control and the obese group have been published elsewhere [1,6].…”
Section: Postural Sway Protocolmentioning
confidence: 99%
“…These individuals sway more than persons with a lower BMI (<25 kg m À2 ) during normal quiet standing [1][2][3] and weight loss has been shown to reduce the magnitude and speed of their postural sway [4]. Why these individuals oscillate more than normal weight individuals remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It has, however, been shown that *Address correspondence to this author at the Department of Physiotherapy, Sahlgrenska University Hospital, 413 45 Gothenburg, Sweden; Tel: 0046 31 3421195; Fax: 0046 31 342 43 41; E-mail: malin.wiklund@vgregion.se in men this intervention is associated with a significant decline in muscular strength, particularly in the lower limbs, one year after surgery [3].…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Weight loss, however, is also accompanied with a loss of absolute muscular strength and sometimes improvement in relative muscular strength. 23 Therefore, one may propose that weight loss induces a gain in relative muscular strength which could lead to improved balance control. We hypothesize that improved balance control following weight loss would be due to improved relative muscular strength (that is, muscular strength is important for balance control in overweight and obese individuals).…”
Section: Introductionmentioning
confidence: 99%